Effect of Pyrasulfotole Carryover to Peanut and Tobacco. (7th September 2017) - Grey, Timothy L.; Diera, Alexx; Moore, J. Michael; Rucker, Keith S.; Butts, Christopher L.
Abstract : In the southeastern United States, growers often double-crop soft red winter wheat with peanut. In some areas, tobacco is also grown as a rotational crop. Pyrasulfotole is a residual POST-applied herbicide used in winter wheat, but information about its effects on rotational crops is limited. Winter wheat planted in autumn 2014 was treated at Feekes stage 1 or 2 with pyrasulfotole at 300 or 600 g ai ha −1 . Wheat was terminated by glyphosate at Feekes stage 3 to 4. Peanut was planted via strip tillage, while tobacco was transplanted into prepared beds after minimal soil disturbance. Peanut exhibited no differences in stand establishment, growth, or yield, and tobacco stand, growth, and biomass yields were not different from the nontreated control for any pyrasulfotole rate or treatment timing.